American Cancer Society's report on the status of cancer disparities in the United States, 2021. (8th December 2021) - Islami, Farhad; Guerra, Carmen E.; Minihan, Adair; Yabroff, K. Robin; Fedewa, Stacey A.; Sloan, Kirsten; Wiedt, Tracy L.; Thomson, Blake; Siegel, Rebecca L.; Nargis, Nigar; Winn, Robert A.; Lacasse, Lisa; et al.
Abstract: In this report, the authors provide comprehensive and up‐to‐date US data on disparities in cancer occurrence, major risk factors, and access to and utilization of preventive measures and screening by sociodemographic characteristics. They also review programs and resources that have reduced cancer disparities and provide policy recommendations to further mitigate these inequalities. The overall cancer death rate is 19% higher among Black males than among White males. Black females also have a 12% higher overall cancer death rate than their White counterparts despite having an 8% lower incidence rate. There are also substantial variations in death rates for specific cancer types and in stage at diagnosis, survival, exposure to risk factors, and receipt of preventive measures and screening by race/ethnicity, socioeconomic status, and geographic location. For example, kidney cancer death rates by sex among American Indian/Alaska Native people are ≥64% higher than the corresponding rates in each of the other racial/ethnic groups, and the 5‐year relative survival for all cancers combined is 14% lower among residents of poorer counties than among residents of more affluent counties. Broad and equitable implementation of evidence‐based interventions, such as increasing health insurance coverage through Medicaid expansion or other initiatives, could substantially reduce cancer disparities. However, progress will require not only equitable local, state, and federal policies but also broad interdisciplinary engagement to elevate and address fundamental social inequities and longstanding systemic racism.